ANALISIS PENGARUH REWARD KARYAWAN TERHADAP MOTIVASI KERJA DI DEPARTEMENFOOD AND BEVERAGES COUNTYARD BY MARRIOTT BALI SEMINYAK RESORT - Devi Pudarika; Roels Ni Made Sri Puspadewi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine whether rewards have an influence on employee motivation to work, especially at Courtyard by Marriott Bali Seminyak Resort. This study used a quantitative method where the sample was taken using the entire population, amounting to 72 and using a non- probability sampling technique, namely saturated sampling. Data collection was carried out by conducting questionnaires, interviews, and observations. The distributed questionnaire consisted of 27 statements using a Likert scale and the results of the questionnaire were processed with a tool in the form of SPSS version 26. The results of the research that has been obtained are that the majority have an age range of 20-30 years with a working period of 1-3 years. Based on the validity and reliability tests of all statements used are valid and reliable. Reward can explain 50.5% of work motivation variables, while the remaining 49.5% is influenced by other variables not explained in this study. Based on the simple linear regression test, the significance value shows the number .009 which is greater than the significance level. Through the results of the T test, it can be seen that the reward variable affects work motivation. Based on the results of this study, the suggestions that can be conveyed are not to overly impose the way employees work in completing each task and to be able to provide direction